Beiträge zur Compoundierung von Wood-Plastic-Composites (WPC) - Böhm, Nils

Theoretische und experimentelle Untersuchungen zum Temperatur- und Durchsatzverhalten von Kautschukextrudern - Brockhaus, Sebastian

Weiterentwicklung Netzwerktheorie basierender Werkzeugauslegung - Jacobkersting, Bianca

Dimensional Tolerances for Additive Manufacturing: Fused Deposition Modeling - Knoop, Frederick; Lieneke, Tobias (Inside 3D Printing 2017)

Reproduzierbarkeit der Maßhaltigkeit im Fused Deposition Modeling - Knoop, F.; Lieneke, Tobias; Schöppner, Volker (Rapid Tech - International Trade Show & Conference for Additive Manufacturing)
Fused Deposition Modeling (FDM) is used for prototypes, single-partproduction and small batch productions of thermoplastic components. This manufacturing technique has the huge benefit that no forming tool is needed. The knowledge about dimensional deviations which occur in the FDM process is necessary for calculating fits and for determining tolerances. A major challenge is the reproducibility of the dimensional accuracy of FDM parts and the reproducibility between different FDM machines. There are many influential factors on the dimensional accuracy in the FDM process for example geometric, material-specific or process-specific factors, which are considered in this paper. The influence of the part position on the build platform of a Stratasys Fortus 400mc is analyzed in terms of the achievable dimensional accuracy. For this purpose, the temperature distribution in the actively heated build chamber is investigated and possible correlations to the dimensional accuracy are identified. The reproducibility of one machine is examined by a multiple production of the test specimens. In addition, a comparison with three other FDM machines from Stratasys is made. Afterwards, the long-term reproducibility of the dimensional accuracy is verified to consider how environmental influences such as maintenance or modification of machine components affect the dimensional accuracy of the FDM process.

Considering machine- and process-specific influences to create custom-built specimens for the Fused Deposition Modeling process - Schumacher, C.; Schöppner, Volker; Guntermann, J. (28th Annual International Solid Freeform Fabrication Symposium)
Compared to conventional polymer processing technologies the material selection in the Fused Deposition Modelling (FDM) process is restricted. To expand the range of materials the requirements for the material properties and the semi-finished products (filaments) must be clarified. For this, a machine- and process-independent rating of the processability is necessary. The established standards for the tensile strength test apply to specimens with nearly isotropic mechanical properties. The FDM process generates anisotropic parts. The properties are mainly influenced by the machine quality and the data processing. It is not possible to test a material for FDM independently of the machine and the data processing. In this paper, machine and process specific influences are investigated. Considering these influences, a custom-built specimen is created to test the tensile strength of the welding seams for polyamide 6. This procedure allows a machine- and process-independent rating of the processability in terms of tensile strength for different materials.

Geometrical Accuracy of Holes and Cylinders Manufactured with Fused Deposition Modeling - Knoop, F.; Schöppner, Volker (28th Annual International Solid Freeform Fabrication Symposium)
A widely used Additive Manufacturing (AM) technology is Fused Deposition Modeling (FDM) to create prototypes and end-use parts with close-to-production thermoplastics. For their use as a final product, it is necessary that additively manufactured parts strictly adhere to the geometrical requirements of the technical drawing. In this paper, the holes and cylinders of the cylindrical elements are investigated in terms of achievable geometrical accuracy. For this purpose, different test specimens that allow a measurement of inner and outer diameters from 3 to 80 mm were designed. All specimens were measured with a coordinate measuring machine (CMM) to evaluate deviations from the nominal dimension and form deviations. The measuring method includes a scanning of the surface to record the course of dimensional deviations over the diameter. Thus, it was possible to visualize how deviations on cylindrical elements manufactured in FDM occur. In order to counteract these deviations and to improve the dimensional accuracy, different shrink factors and filling patterns were investigated. Consequently, an improvement of the dimensional accuracy was achieved.

Beurteilung der Schweißnahtfestigkeiten verschiedener Kunststoffe im FDM-Prozess - Schöppner, Volker; Schumacher, C.; Guntermann, J. (Jahresmagazin Kunststofftechnik)
Um die Materialauswahl für den FDM-Prozess zu steigern, sollten die durch den FDM-Prozess an das Material gestellten Anforderungen bekannt sein. Dazu ist eine von der Maschine und der individuellen Datenaufbereitung möglichst unabhängige Bewertung der FDM-Verarbeitungseignung wünschenswert. In diesem Artikel werden eine Prüfmethode und ein dazu entwickelter Probekörper vorgestellt, mit dem die Schweißnahtfestigkeit verschiedener Polyamid 6 Typen im FDM-Prozess ermittelt und verglichen wird.

Universal Micromachining Platform and Basic Technologies for the Manufacture and Marking of Microphysiological Systems - Moritzer, Elmar; Hirsch, André; Günther, K.; Sonntag, F.; Klotzbach, U.; Lasagni, A.F. (Micromachines)
Micro Physiological Systems (MPS), also known as Multi-Organ-Chip, Organ-on-a-Chip, or Body-on-a-Chip, are advanced microfluidic systems that allow the cultivation of different types of cells and tissue in just one common circuit. Furthermore, they thus can also adjust the interaction of these different tissues. Perspectival MPS will replace animal testing. For fast and flexible manufacturing and marking of MPS, a concept for a universal micromachining platform has been developed which provides the following latest key technologies: laser micro cutting of polymer foils, laser micro- and sub-micro-structuring of polymer foils, 3D printing of polymer components as well as optical inspection and online process control. The combination of different laser sources, processing optics, inspection systems, and print heads on multiple axes allows the change and exactly positioning to the workpiece during the process. Therewith, the realization of MPS including 3D printed components as well as direct laser interference patterned surfaces for well-defined cell adhesion and product protection is possible. Additional basic technologies for the generation of periodical line-like structures at polycarbonate foils using special Direct Laser Interference Patterning (DLIP) optics as well as for the 3D printing of fluid-tight cell culture reservoirs made of Acrylonitrile Butadiene Styrene directly onto polycarbonate microfluidics were established. A first prototype of the universal micromachining platform combining different lasers with Direct Laser Writing and DLIP is shown. With this laser micro cutting as well as laser micro-structuring of polycarbonate (PC) foils and therewith functionalization for MPS application could be successfully demonstrated.

Fatigue Behavior of FDM Parts Manufactured with Ultem 9085 - Fischer, M.; Schöppner, Volker (JOM: The Journal of The Minerals. Metals & Materials Society (TMS))
The mechanical characterization of fused deposition modeling (FDM) parts is mostly done by static tests. In many applications, parts are also dynamically loaded. Here, fatigue tests can help to identify the expected lifetime of a part. This article discusses the fatigue behavior of FDM specimens manufactured with Ultem 9085. For this, tensile bars are manufactured according to ASTM D638 in different build orientations. Tests are performed in a range of pulsating tensile stresses, and S-N curves are documented for different build orientations. For higher loads, the FDM anisotropy characterizes the lifetime of used specimens, which is similar to static tensile bars. For lower loads, including a higher number of cycles to failure, S-N curves of different build orientations converge. In further tests, tensile bars were chemically smoothed with chloroform vapor. Chemical smoothing reduces surface roughness and increases tensile strength of specimens in the upright build direction. Fatigue tests of chemically treated specimens show no significant lifetime increase.

Quality Improvement of FDM Parts by Parameter Optimization - Knoop, F.; Kloke, A.; Schöppner, Volker (32nd International Conference of the Polymer Processing Society)
Fused Deposition Modeling (FDM) is an Additive Manufacturing (AM) technology which is used for prototypes, single-part-production and also small batch productions. For use as a final product, it is important that the parts have good mechanical properties, a high dimensional accuracy and smooth surfaces. The knowledge of the mechanical properties is very important for the design engineer when it comes to the component design. In this paper, investigations were conducted with the polymer ABS-M30 from Stratasys Inc. To achieve a quality improvement of FDM parts, various toolpath parameters and orientations were used. Within the mechanical properties, the tensile, flexural and impact strength were evaluated. Furthermore, the tensile strength of FDM parts is compared to injection molded specimens. With optimized parameters, an increase of the tensile strength by up to 28 % and a doubling of the impact strength were possible.

Bestimmung der Mischgüte bei Kautschukstiftextrudern auf Basis experimenteller und simulativer Methoden - Schöppner, Volker; Schadomsky, Michael; Walter, J. (25. Fachtagung Technomer)

Investigation of Residual Stress in Laser Transmission Welding of Polypropylene - Schöppner, Volker; Lakemeyer, P.; Wübbeke, Andrea; Geißler, S.; Schmidt, M. (70th Annual Assembly of the International Institute of Welding (IIW))

Untersuchung der Werkstoff-, Prozess- und Bauteileigenschaften beim Fused Deposition Modeling Verfahren - Kloke, Agnes
In dieser Arbeit wurde ein Prozessverständnis für das FDM-Verfahren hinsichtlich der Verarbeitung des Materials Ultem*9085 aufgebaut. Es wurde der Einfluss des Materials, des Prozesses und der Maschine auf die resultierende Bauteilqualität untersucht. Die Materialqualität unterschiedlicher Chargen zeigt, dass Feuchtigkeit im Material die Strangablage beeinflusst. Die Analyse der Prozessparameter, die anhand der Kurzzeitfestigkeiten analysiert wurden, zeigt einen starken Einfluss der Aufbauorientierung. Mittels einer Parameteroptimierung können ferner gleiche Festigkeitswerte wie aus dem Spritzgießprozess erreicht werden. Bei der Untersuchung der Langzeitfestigkeiten wurde festgestellt, dass sich die Festigkeitswerte bei unterschiedlichen Umgebungsbedingungen nicht ändern. Die Untersuchung einiger Anlagenkomponenten auf die resultierende Oberflächengüte, Geometriegenauigkeit und Festigkeitseigenschaften kann den Einfluss von u. a. der Bauraum- sowie der Düsentemperaturen auf die Bauteilqualität zeigen. Zuletzt wurde die Möglichkeit einer Leichtbauanwendung anhand von Sandwich-Prüfkörpern untersucht. Hierbei beeinflussen sowohl die verfahrensunabhängige Mechanik als auch die verfahrensspezifischen Effekte die Festigkeitswerte.

A New Sample Preparation Method to Investigate Melting Phenomena within a Partly Filled Melting Zone Of Co-Rotating Twin Screw Extruders - Schöppner, Volker; Westhues, K.; Westhues, T (32nd International Conference of the Polymer Processing Society (PPS))

An Approach to Non-Destructive Testing of Aged Polymers - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (32nd International Conference of the Polymer Processing Society (PPS))

Auswirkungen von Betriebsparametern in der Heißluftvulkanisation - Schöppner, Volker; Brockhaus, S.; Penner, C.; Möckel, J. (GAK Gummi Fasern Kunststoffe)

Berechnung des Materialabbaus von PP und PS in der Plastifiziereinheit Teil 1: Belastung und Materialmodellierung - Schöppner, Volker; Littek, S.; Döring, Artjom; Kuckling, Dirk (Zeitschrift Kunststofftechnik / Journal of Plastics Technology)

Detecting Molecular Damage - Non-Destructive Characterization of Molecular Changes in Aged Polymers - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (Kunststoffe international)

Development of an Inline Plasma Treatment During Injection Molding Process - Moritzer, Elmar; Nordmeyer, T.; Enneking, L.; Grishin, A.; Knospe, A.; Buske, C. (74th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Die Riveting – A New Joining Technology for Composite Sheet-Metal-Hybrid Joints - Moritzer, Elmar; Budde, C.; Hüttner, M. (Joining in Car Body Engineering 2016)

Ein Ansatz zur zerstörungsfreien Prüfung von hydrothermisch gealterten Polymeren - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (Safe and Reliable Structures)

Experimental Investigations on the Fibre Length Degradation in Injection Moulds - Moritzer, Elmar; Martin, Y. (32nd International Conference of the Polymer Processing Society (PPS))

Fiber Length Degradation of Glass Fiber-Reinforced Polypropylene during Shearing - Moritzer, Elmar; Brockhaus, S.; Heiderich, G. (74th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Fiber Length Degradation of Glass Fiber-Reinforced Polypropylene during Shearing - Moritzer, Elmar; Brockhaus, S.; Heiderich, G. (16th Annual International Polymer Colloquium (IPC))

Fiber Length Reduction during Shearing in Polymer Processing - Moritzer, Elmar; Heiderich, G. (32nd International Conference of the Polymer Processing Society (PPS))

First Insight into the High Speed Extrusion of Polycarbonate - Schöppner, Volker; Pohl, M. (32nd International Conference of the Polymer Processing Society (PPS))

Gut gewickelt - Mit effektiver Topologieentwicklung zur belastungsorientierten Bauteilgeometrie einer Kunststoffspule für die Monofilindustrie - Moritzer, Elmar; Kleeschulte, R.; Zavoral, S.; Kaiser, E. (Kunststoffe)

In Zukunft einfach entformen - Neu entwickelte molekulare Beschichtungen sollen die Entformungskräfte beim Spritzgießen verringern - Moritzer, Elmar; Fecke, N.; Landgräber, B.; Kern, W.; Kaynak, B.; Grundmeier, Guido; Waschke, S. (Kunststoffe)

Influence of the Initial Fiber Orientation on the Weld Strength in Welding of Glass Fiber Reinforced Thermoplastics - Schöppner, Volker; Fiebig, I. (International Journal of Polymer Science)

Investigation on Factors Influencing Fiber Orientation in Welding of Fiber Reinforced Thermoplastics - Schöppner, Volker; Fiebig, I. (69th Annual Assembly of the International Institute of Welding (IIW))

Investigations of the Influence of Material and Pellet Shape on the Dissipation in the Solids Conveying Zone of Single-Screw Extruders Based on the Discrete Element Method - Schöppner, Volker; Trippe, J. (32nd International Conference of the Polymer Processing Society (PPS))

Spritzgießdirektcompoundierung (SGDC) - Produktspezifische Materialentwicklung im Spritzgießprozess - Moritzer, Elmar; Martin, Y.; Müller, E. (Kunststofftechnik - Spritzgießen 2016)

Melting Phenomena and Sample Preparation Method within a Partly Filled Melting Zone of Co-Rotating Twin Screw Extruders - Schöppner, Volker; Westhues, K.; Westhues, T. (74th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Modellierung des Glasfaserlängenabbaus - Schöppner, Volker; Kloke, P.; Westhues, K. (PolyMerTec 2016)

Molekularen Schäden auf der Spur - Zerstörungsfreie Charakterisierung molekularer Veränderungen in gealterten Polymeren - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (Kunststoffe)

Non-Destructive Characterization of Hygrothermally Aged Polymers - Schöppner, Volker; Hüttner, M.; Henning, Bernd; Webersen, Manuel (74th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Organoblechnieten - Moritzer, Elmar; Budde, C.; Hüttner, M. (22. Nationales Symposium SAMPE (Society for the Advancement of Material and Process Engineering) Deutschland e.V.)

Partikel und Schmelze im dynamischen Netz - Schöppner, Volker; Herken, T.; Sporkmann, F.; Platte, F. (Kunststoffe)

Plasmaunterstütztes Fügen von Kunststoffen - Moritzer, Elmar; Schöppner, Volker; Lakemeyer, P.; Nordmeyer, T. (Joining Plastics)

Quality Improvement of FDM Parts by Parameter Optimization - Schöppner, Volker; Bagsik, A.; Knoop, F. (32nd International Conference of the Polymer Processing Society (PPS))

Realitätsnah und definiert verschmutzen - Schöppner, Volker; Meilwes, P. (Kunststoffe)

Schweißen von faserverstärkten Kunststoffen: Erhöhung der Wirksamkeit der Faserverstärkung in der Schweißnaht - Schöppner, Volker; Fiebig, I. (Jahresmagazin Kunststofftechnik)

Several Influences during Examinations of Laser Transmission Welding - Current Status - Schöppner, Volker; Fiebig, I.; Lakemeyer, P.; Bates, P.; Zazoum, B.; Zak, G.; DuQuesnay, D. (69th Annual Assembly of the International Institute of Welding (IIW))

The Development of a Non-Destructive Testing Method for the Characterization of Hygrothermally Aged Polymers - Moritzer, Elmar; Fiebig, I.; Hüttner, M.; Henning, Bernd; Webersen, Manuel (69th Annual Assembly of the International Institute of Welding (IIW))

The Influence of Welding Processes on the Weld Strength of Flame-Retardant Materials - Schöppner, Volker; Evers, F.; Lakemeyer, P. (Welding in the World)

Ultraschallbasierte Charakterisierung von gealterten Polymeren - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (Jahresmagazin Kunststofftechnik)

Zerstörungsfreie Charakterisierung des hydrothermischen Alterungsverhaltens von Polymeren - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (18. GMA/ITG Fachtagung Sensoren und Messsysteme)

Alterung spritzgegossener thermoplastischer Mikrobauteile - Meister, Steve

Einfluss der Nanopartikelgeometrie auf ie Buchzähigkeit und das Ermüdungsrissausbreitungsverhalten von Epoxidharzen - Kothmann , Martin H.